Evaluation of the Implementation of Field Work Practices Using the CIPP Model - Widiyanti, Rusi; HS, Sufyati; Rosita, Tita (Yayasan Sinergi Kawula Muda, 2024)
Based on initial observations carried out at I, the results showed that as many as 70% of students did not understand the Field Work Practice procedures, where the Field Work Practice activity schedule was not immediately socialized at the beginning of the semester. Job on training program (PKL) are an important part of the process in implementing education at vocational schools. The aim of the PKL is to increase the competency of vocational school students in accordance with the needs of the industrial world. This research aims to evaluate the implementation of PKL to determine the suitability of implementing the PKL with the CIPP (Context, Input, Process, Product) model. Researchers used qualitative methods, data was obtained from interview data with relevant respondents at SMKN 1 Rejotangan and SMKN 2 Tulungagung and also through literature study and documentation that supports this research. Evaluation of the Context of the On job training program for Vocational School Students Competency in Office Automation and Management Skills, the relevance of the PKL Program to the school curriculum and the needs and opportunities as a Program follow-up from street vendors has been carried out well. Evaluation of Inputs which includes the readiness of students. Evaluation of the process which includes student participation, utilization of time for implementing PKL. Evaluation of the implementation which includes increasing student competency after carrying out PKL and the impact of this PKL activity on the student's job placement after graduating from school has been achieved with Good.